2013
DOI: 10.5539/gjhs.v5n3p150
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleepiness and Quality of Sleep in Patients with COPD Compared to Control Group

Abstract: Objectives:Chronic obstructive pulmonary disease (COPD) is a widespread disease. It produces some night symptoms such as nighttime cough and dyspnea. Then subjective and objective changes in sleep pattern are expected. Present study was conducted to determine frequency of sleepiness and quality of sleep in patients with COPD.Materials & Methods:Present case-control study has been performed on 120 patients with diagnosis of COPD who had been referred to pulmonary disease clinic in a University teaching hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
(30 reference statements)
2
19
0
Order By: Relevance
“…However these groups of patients were small and age and gender distributions were not homogeneous. In the present study we observed a similar prevalence of poor sleep quality that has been reported previously for patients with chronic lung disease using the PSQI score as to 67.9% and 70.0% in COPD respectively [30,31].…”
Section: Prevalence Of Poor Sleep Qualitysupporting
confidence: 91%
“…However these groups of patients were small and age and gender distributions were not homogeneous. In the present study we observed a similar prevalence of poor sleep quality that has been reported previously for patients with chronic lung disease using the PSQI score as to 67.9% and 70.0% in COPD respectively [30,31].…”
Section: Prevalence Of Poor Sleep Qualitysupporting
confidence: 91%
“…Studies that examined differences in PSQI global score between healthy subjects and patients suffering from a variety of disorders known to be associated with poor sleep, showed significant differences between groups [9,22,45,49,51,56,60,68,71,79]. Studies that examined differences within groups of people (i.e., race, age, sex, different symptom clusters within the same population, etc.)…”
Section: Known-group Validitymentioning
confidence: 99%
“…[22,46,51,56,69,79]. The clinical samples combined comprised 538 individuals, and the non-clinical samples e 745 individuals.…”
mentioning
confidence: 99%
“…They found significantly more subjects suffering from excessive daytime sleepiness among COPD patients than among controls. Patients with moderate COPD seemed to be the most affected [16]. …”
Section: Introductionmentioning
confidence: 99%